Automated PV Irrigation System for Red Chili - Mohamed, Nor Aeinul Mardhiah; Hamdan, Rohaiza (Evolution in Electrical and Electronic Engineering, 2025)
This paper presents the development of an automated photovoltaic (PV) irrigation system designed specifically for red chili cultivation. The system combines renewable energy with IoT-based real-time monitoring to enhance water efficiency and support sustainable farming. A 50W solar panel powers essential components including the ESP32 microcontroller, soil moisture and rain sensors, and a DC water pump. The system intelligently controls irrigation based on real-time soil moisture and rain detection, reducing water wastage. Monitoring and alerts are managed via Blynk and Telegram. Experimental results under different solar panel orientations (horizontal, vertical, 45°) show that optimal performance is achieved at a 45° angle. This integration enables low-cost, efficient irrigation suitable for small-scale farmers, aligning with sustainable agricultural goals